Art and Androgyny: The Aerialist - Naomi Ritter (Studies in 20th & 21st Century Literature, 1989)
Among the many circus performers who have fascinated writers and artists since Romanticism, the clown and the aerialist predominate. In the nineteenth century, the tightrope artiste inspired comparisons with the (self-styled) equally daring and equally craftsmanlike poet. The vertical metaphor suggested a vision of transcendent art that Romantics and their heirs claimed for themselves. In the twentieth century, vestiges of the same identification and transcendence remain, but a new sexual focus appears also. Two important texts by Cocteau and Thomas Mann, "Le Numero de Barbette" (1926) and Chapter 1 in Book III of Felix Krull ( 1951), show the aerial artiste as sexually ambivalent. An intertextual discussion of these two works highlights unnoted similarities in the seemingly opposed aesthetics of the two writers.
Keywords: circus performers; artists; art; Romanticism; clown; aerialist; predominate; nineteenth century; tightrope; tightrope artiste; poet; vertical metaphor; metaphor; transcendent art; Romantics; twentieth century; sexual; Cocteau; Thomas Mann; Le Numero de Barbette; Felix Krull; sexually ambivalent